ANALISIS PERBANDINGAN METODE SAW, WP DAN SMART UNTUK PEMILIHAN “SEPEDA MOTOR YAMAHA MATIC 125 CC” - Mahasinul Akhlak, Muhammad Lutfi; Revina, Anastasia; Anthony, Lukas; Oktavia, Nova; Sukma, Anniza (TRANSFORMASI, 2023)
For prospective buyers who don't understand the ins and outs of motorbikes, choosing a 125 cc automatic motorbike is not easy. Therefore, a reference is needed as a rationale for selecting it. There are several criteria that are used as a benchmark when choosing an automatic motorbike, including price, quality, popularity, fuel consumption, spare parts and appearance. This research offers a solution in selecting a used motorbike using the Smart, WP and SAW methods which are expected to help prospective buyers in selecting a 125 cc automatic motorbike. Based on the results of the calculation of the assessment criteria factors submitted to the system, the determination of the 125 cc automatic motorbike is obtained by calculating the priority weight values for selecting alternative 125 cc automatic motorbikes to be purchased. The research results show that the SAW method gets a percentage value of 99.07671667, the WP method gets a percentage value of 99.88888889 while the SMART method gets a percentage value of 75.61111111. Then the highest weight ranking is the Yamaha Mio M3 125cc motorbike at 0.146742631 Keywords: motorbike, matic 125cc, SMART, WP, SAW